Temporal Correlation between Social Tags and Emerging Long-Term Trend Detection - Hsu, Ming-Hung; Chang, Yu-Hui; Chen, Hsin-Hsi (Proceedings of the International AAAI Conference on Web and Social Media, 2010)
Social annotation has become a popular manner for web users to manage and share their information and interests. While users' interests vary with time, tag correlation also changes from users' perspectives. In this work, we explore four methods for estimating temporal correlation between social tags and detect if a long-term trend emerges from the history of temporal correlation between two tags. Three types of trends are specified: steadily-shifting, stabilizing, and cyclic. To compare the results of the four estimation methods, an indirect evaluation is realized by applying detected trends to tag recommendation.